The Heart of a Mother, The Waves of Mothering: A Narrative Inquiry into Mothering Experiences of Child Weight Management - Fierheller, Dianne (My University, 2022)
Many stories exist within the professional landscape of child weight management programming and health services. Grand narratives within these spaces story fat bodies as “unhealthy”, “risky” and in need of transformation, and often position the family and mothers in particular given gendered caregiving norms, as responsible for their children’s weight and poor health. Mothering stories and experiences are rarely told by the mothers themselves within this professional landscape. This study is a narrative inquiry that explores the in-depth experiences of two mothers who previously participated with their children in an Ontario paediatric weight management program. Given my work as a social worker within child weight management clinics I also explore my experiences alongside the participants. Clandinin and Connelly’s conceptualization of narrative inquiry and the three dimensional framework of temporality (past, present, future), sociality and place, inquiring inward, outward, backward and forward, were used in order to find meaning in mothering experiences of child weight management. Narrative beginnings share my own experiences of mothering and child weight management. Relational ethics were central as the inquiry unfolded, allowing for simultaneous exploration of experiences, continuous negotiation, awareness and re-evaluation with each mother, from recruitment, field work, to field text, interim text and the writing of the final text. Given the current social distancing restrictions related to the COVID-19 pandemic, conversations took place over zoom and telephone and were audio-recorded and transcribed verbatim. Detailed narrative accounts were written for each mother capturing individual experiences of child weight management as they intersected with many other experiences in their everyday lives. Narrative threads weaved together the mother’s experiences throughout the inquiry and focused on disrupting the grand narrative and resisting fragmentation. The inquiry contributes to the scholarship within fields of social work, social justice, mothering and health care by providing new ways of knowing about and engaging in conversations about mothering, weight, fatness and health.
Keywords: Mothering experiences; Child weight management; Narrative Inquiry